A DPSR and SEM Based Framework to Evaluate High-Quality Development in Chinese Manufacturing Industry - Fen Lyu; Gang Wu (SAGE Open, 2023)
China’s manufacturing industry has emerged as a major contributor to both the nation’s economic growth and global trade. Achieving high-quality development in this sector is not only crucial for China’s sustainable progress but also holds significant implications for the global economy. Considering the importance of Chinese manufacturing industry, this paper establishes a framework for exploring the mechanism of manufacture industry’s high-quality development in China’s three economic regions based on the Driver-Pressure-State-Response (DPSR) model and Structural Equation Modeling (SEM). SEM is established for analyzing the multiple paths of manufacture industry’s high-quality development in the eastern, middle and western economic region of China. The findings reveal distinct patterns in each region. In the eastern region, a unidirectional path of “Driver-Pressure-State-Response” is confirmed, with a particular emphasis on quality improvement and efficiency increase. The middle region exhibits a leapfrog path characterized by “Driver-Pressure-State” and “Pressure-Response,” where quality improvement and dynamic conversion play critical roles. Conversely, the western region demonstrates an interrupt path of “Pressure-State-Response,” highlighting the significance of structural rationalization and dynamic conversion. Based on these results, sustainable solutions and suggestions for promoting high-quality development in the manufacturing industry are proposed, providing valuable targeted insights for the transformation and advancement of China's manufacturing sector. This study makes a novel contribution by developing a DPSR-SEM model and expands literature and knowledge in high-quality development of manufacturing industry. Practically, this study can guide decision-makers, managers, and stakeholders in understanding the interactions between driving forces, pressures, states, and responses in the context of manufacturing industry.